Electrophysiological aspects of schizophrenia - Begić, Dražen (Array, 1998)
Quantitative EEG was observed in 25 patients with positive and 25 patients with negative schizopfrenia. Positive and negative schizophrenia were found to differ only in the delta and theta bands over frontal regions.